Effects of the „Polish Deal” Programme on Local Government Units - Hajdys, Dagmara (Journal of Finance and Financial Law, 2021)
The aim of this paper is to present the „Polish Deal” program in the context of its influence on budget management of local government units. The paper puts forward a thesis that changes in the tax system, as specified in the „Polish Deal” programme, will have a negative impact on the finances of local government units. The study was based on selected literature, documents on the financial perspective for 2021–2027, the „Polish Deal” programme, financial information on the state of finances of local government units in 2018–2020 and opinions of the Union of Polish Metropolises and the Association of Polish Cities to the draft Polish Deal programme. The period of the SARS-CoV-2 pandemic coincided with the beginning of the next financial perspective in the European Union for the years 2021–2027. EU institutions have prepared a number of instruments relevant to the post-pandemic era, including the Next Generation EU. At the same time, they imposed on Member States the obligation to prepare their own post-pandemic plans. Poland prepared the National Recovery Plan. This was followed by the government’s presentation of the „Polish Deal” program, which is a promise of socio-economic reforms. The projects included in the „Polish Deal”, in many areas will require the activity and involvement of local authorities. The effects of these activities will be not only financial but also organizational, which will translate into increased spending. Changes in the tax system, especially in the personal income tax, will considerably affect revenues from PIT shares, which will disturb the stability of territorial self-government units’ financial system. Therefore, it is necessary that the government and self-government representatives jointly work out solutions, which will guarantee the compensation of losses for the self-governments in a long-term, and a stable way to restore the principle of adequacy.